2001
DOI: 10.1002/jcp.10043
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the V3 variant of versican alters arterial smooth muscle cell adhesion, migration, and proliferation in vitro

Abstract: Versican is an extracellular matrix proteoglycan produced by many cells. Although versican is generally known as a large chondroitin sulfate proteoglycan (CSPG), the smallest splice variant, V3, consists only of the amino- and carboxy-terminal globular domains and is therefore predicted to be a small glycoprotein, lacking CS chains. The large size, negative charge, and ability of versican variants to form pericellular coats with hyaluronan are responsible for many of its effects. V3, lacking the large size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 36 publications
6
100
1
5
Order By: Relevance
“…In our previous study, 11 we reported on the reduced pericellular coat in cultured V3-transduced ASMCs and hypothesized that this phenotypic feature might arise through properties associated with the G1 domain of V3 that contains the HAbinding region. The larger versican variants V0 and V1, with their attached chondroitin sulfate chains, bind to HA to form pericellular coats that are antiadhesive and necessary for both proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, 11 we reported on the reduced pericellular coat in cultured V3-transduced ASMCs and hypothesized that this phenotypic feature might arise through properties associated with the G1 domain of V3 that contains the HAbinding region. The larger versican variants V0 and V1, with their attached chondroitin sulfate chains, bind to HA to form pericellular coats that are antiadhesive and necessary for both proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…11 Compared with vector-alone cells, V3 cells were more spread, flatter, and less spindle-shaped (Figure 1). The most notable difference, however, and one not seen in short-term cultures, was the presence of an irregular network of fibers, especially prominent around the periphery of cells adherent to the culture dish (Figure 1).…”
Section: Morphology Of Long-term Culturesmentioning
confidence: 98%
See 2 more Smart Citations
“…Expression of V3 in ASMCs-The V3 splice variant of versican was expressed in Fischer rat ASMCs using retroviral vectors, as described previously (17)(18)(19). Briefly, the rat V3 sequence was inserted into the BamHI site of the retroviral vector LXSN (courtesy of Dr. A. D. Miller, Fred Hutchinson Cancer Research Center, Seattle, WA).…”
Section: Methodsmentioning
confidence: 99%